Diagnostic and Therapeutic Roles of Endoscopic Ultrasound in Pediatric Pancreaticobiliary Disorders. Issue 2 (August 2015) - Scheers, Isabelle; Ergun, Meltem; Aouattah, Tarik; Piessevaux, Hubert; Borbath, Ivan; Stephenne, Xavier; De Magnée, Catherine; Reding, Raymond; Sokal, Etienne; Veyckemans, Francis; Weynand, Birgit; Deprez, Pierre H.
ABSTRACT Objectives: The diagnostic role of endoscopic ultrasound (EUS) in children has only recently been demonstrated, and that also to a lesser extent than in adults. Data on the technique's therapeutic indications remain scarce. We therefore sought to evaluate diagnostic and interventional EUS indications, safety, and impact in children with pancreaticobiliary disorders. Methods: We retrospectively reviewed our single pediatric center records, covering a 14-year period. Results: From January 2000 to January 2014, 52 EUS procedures were performed in 48 children (mean age: 12 years; range: 2–17 years) with pancreaticobiliary disorders for the following indications: suspected biliary obstruction (n = 20/52), acute/chronic pancreatitis (n = 20), pancreatic mass (n = 3), pancreatic trauma (n = 7), and ampullary adenoma (n = 2). EUS was found to have a positive impact in 51 of 52 procedures, enabling us to avoid endoscopic retrograde cholangiopancreatography (ERCP) (n = 13 biliary; n = 6 pancreatic), focusing instead on endotherapy (n = 7 biliary; n = 14 pancreatic) or reorienting therapy toward surgery (n = 7). EUS-guided fine-needle aspiration was carried out on 12 patients for pancreatic tumor (n = 4), pancreatic cyst fluid analysis (n = 4), autoimmune pancreatitis (n = 2), and suspicion of biliary tumor (n = 2). A total of 13 therapeutic EUS procedures (11 children) were conducted, including 9 combined EUS–ERCP procedures (7 children, mean age: 8 years, range: 4–11 years), 3 EUS-guided pseudocyst drainage (2 children), and 1 EUS-guided transgastric biliary drainage. Conclusions: Our study reports on a large pediatric EUS series for diagnostic and therapeutic pancreaticobiliary disorders, demonstrating the impact of diagnostic EUS and affording insights into novel EUS and combined EUS–ERCP therapeutic applications. We suggest considering EUS as a diagnostic and therapeutic tool in the management of pediatric pancreaticobiliary diseases.